2015
DOI: 10.17795/bhs-32605
|View full text |Cite
|
Sign up to set email alerts
|

Artemisia spicigera Essential Oil: Assessment of Phytochemical and Antioxidant Properties

Abstract: Background: Essential oils (EO), also called volatile odoriferous oil, are aromatic oily liquids extracted from different parts of plants.In general, the constituents in EOs are terpenes, aromatic compounds (aldehyde, alcohol, phenol, methoxy derivatives, and so on), and terpenoids (isoprenoids). Essential Oils have been known to possess antioxidant and antimicrobial activities, thereby serving as natural additives in foods and food products. Objectives: The aim of this study was to assess the quantity and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In one study, phytogenic plant extracts were reported to increase egg production, reduce cholesterol content of serum and yolk, and improve immune response in layers ( Azeke and Ekpo, 2009 ). In another, phytogenic feed additives were reported to have viably positive effect on performance, ovarian morphology, serum lipid parameters, egg sensory quality in laying hens, egg production, and general poultry performance ( Ghajarbeygi et al., 2015 , Wang et al., 2019 ). Such reports on the potential of phytogenic extracts on layer hen performance has therefore stimulated an upsurge of interest in the evaluation of plant essential oils as sources of natural antioxidants and immunopromoting agents ( Bozkurt et al., 2014 , Albour-Elkhair et al., 2018 , Zhai et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In one study, phytogenic plant extracts were reported to increase egg production, reduce cholesterol content of serum and yolk, and improve immune response in layers ( Azeke and Ekpo, 2009 ). In another, phytogenic feed additives were reported to have viably positive effect on performance, ovarian morphology, serum lipid parameters, egg sensory quality in laying hens, egg production, and general poultry performance ( Ghajarbeygi et al., 2015 , Wang et al., 2019 ). Such reports on the potential of phytogenic extracts on layer hen performance has therefore stimulated an upsurge of interest in the evaluation of plant essential oils as sources of natural antioxidants and immunopromoting agents ( Bozkurt et al., 2014 , Albour-Elkhair et al., 2018 , Zhai et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Al-Daraji et al (2011) observed that adding oil in the diet of laying hens increased yolk diameter, yolk weight, albumen diameter, and albumen weight. Linoleic acid has been shown to have a significant favorable influence on interior egg quality and overall poultry performance (Ghajarbeygi et al, 2015;. Kowalska et al (2021) got significantly greater Haugh unit score with dietary addition of soybean meal (SBM) in laying hens in a similar study.…”
Section: Internal Egg Qualitymentioning
confidence: 91%
“…The ethanolic extract was prepared by percolation method as previously described ( 20 ). Next, phenol and flavonoids contents measured ( 21 ). All the extracts were dissolved in distilled water to reach the final concentrations of 0.2, 2, and 20 mg/ml and were stored at 4 °C until use.…”
Section: Methodsmentioning
confidence: 99%